A Rare Case of Swyer Syndrome (BIRDEM Medical Journal, 2019)
Swyer syndrome is caused by abnormal sex differentiation during the embryonic period, resulting in incomplete intrauterine masculinization and undifferentiated gonads. The present case report describes a patient with Swyer syndrome associated with gonadoblastoma. At age of 16 years, this patient reported with primary amenorrhea at Gynae Department of the BIRDEM general Hospital. A physical examination revealed that the patient was at Tanner stage 4 with respect to axillary hair, breasts and pubic hair; she had normal vagina and a small cervix. As her examination findings revealed normal, she was referred to Endocrine outpatient (OPD) for further evaluation. Her karyotyping revealed 46XXY, abdominal ultrasonography revealed adnexal tumor in both sides. On laparotomy, complex tumor was found in both adnexal regions and both ovaries were resected and histopathology revealed gonadoblastoma. The patient was subjected to subsequent chemotherapy. She was treated with a combination of estrogens and progestogens to induce cyclical bleeding, which she discontinued after 3 years. She was lost to follow up for 16 years and again reported to endocrine OPD with irregular menstrual bleeding. Presence of any residual gonadal functional tissue was searched both biochemically and by imaging and the result was negative. Her menstruation was stopped by progestogens and which later on withdrawn successfully without any further onset of menstruation. In conclusion, this report describes an extremely rare case of Swyer syndrome with gonadoblastoma and spontaneous menstruation after a long period of discontinuation of hormone replacement treatment.Birdem Med J 2019; 9(2): 174-176